Kerawang Gayo Cloth's Symbolic Meaning as an Identity of the Gayo Aceh Community - Putra, Iwansyah `; Muharamsyah, Rambang; Khairani, Cut (Universitas Negeri Medan, 2024)
Kerawang Gayo is a traditional cloth used by the Gayo people of Aceh province. The motif of the Kerawang Gayo has a philosophical meaning that has a function that is adjusted to the life of the Gayo people. The purpose of this study is to analyze the symbols found on the Kerawang Gayo cloth along with the meaning of the symbols as a form of the characteristics of the Gayo people. This study is qualitative and uses an ethnographic approach. The data sources in this study are Kerawang Gayo craft workers and the Gayo people from various circles. Data collection techniques in this study are observation, interviews, documents, and artefacts as supporting data such as old and new Kerawang Gayo cloth and Kerawang Gayo carvings. Data analysis in this study begins with domain analysis, taxonomy, components, and cultural analysis. The results of the study show that there are thirteen symbols of the Kerawang Gayo cloth; Emun Berkune, Mata Ni Lo, Puter Tali, Pucuk Ni Rebung, Embun Berangkat, Tekukur motif, Tapak Seleman, Emun Beriring, Rante, Peger, Tali Mestika, Emun Mupesir, and Emun Matumpuk. The influence of nature in Gayo openwork motifs has a fundamental meaning because the traditional patterns and symbolic meanings of the decorative motifs come from the attitudes of the Gayo people. This reflects the conditions and lives of the Gayo people in religion, culture, society, state, nation, democracy, and a sense of responsibility. Each motif found on the Gayo cloth, in addition to having aesthetic value, also has a value for the life of the Gayo people themselves, each motif has a symbol and meaning that describes how the Gayo people live their lives.